Hybrid Atom Tweezer Array of Nuclear Spin and Optical Clock Qubits - Nakamura, Yuma; Kusano, Toshi; Yokoyama, Rei; Saito, Keito; Higashi, Koichiro; Ozawa, Naoya; Takano, Tetsushi; Takasu, Yosuke; Takahashi, Yoshiro (Physical review. X, 2024)
While data qubits with a long coherence time are essential for the storage of quantum information, ancilla qubits are pivotal in quantum error correction (QEC) for fault-tolerant quantum computing. The recent development of optical tweezer arrays, such as the preparation of large-scale qubit arrays and high-fidelity gate operations, offers the potential for realizing QEC protocols, and one of the important next challenges is to control and detect ancilla qubits while minimizing atom loss and crosstalk. Here, we present the realization of a hybrid system consisting of a dual-isotope ytterbium (Yb) atom array, in which we can utilize a nuclear spin qubit of fermionic Yb 171 as a data qubit and an optical clock qubit of bosonic Yb 174 as an ancilla qubit with a capacity of nondestructive qubit readout. We evaluate the crosstalk between qubits regarding the impact on the coherence of the nuclear spin qubits from the imaging light for Yb 174 . For the Hahn-echo sequence with a 399 nm probe and 556 nm cooling beams for Yb 174 , we observe 99.1(1.8)% coherence retained under 20 ms exposure, yielding a discrimination fidelity of 0.9992 and a survival probability of 0.988. The Ramsey sequence with a 556 nm probe beam shows negligible influence on the coherence, suggesting the potential future improvement of low crosstalk measurements. This result highlights the potential of the hybrid-Yb atom array for midcircuit measurements for ancilla-qubit-based QEC protocols.